1996
DOI: 10.1093/brain/119.1.281
|View full text |Cite
|
Sign up to set email alerts
|

Interjoint coordination during pointing movements is disrupted in spastic hemiparesis

Abstract: Approaches to the rehabilitation of movement in spastic hemiparetic patients depend on knowledge of the underlying mechanisms of movement deficits. The goals of this study were to characterize end-point trajectories and interjoint coordination of arm pointing movements to different targets on a horizontal planar surface and to correlate disruptions in motor control in the affected arm of hemiparetic subjects with the level of spasticity and the degree of functional impairment measured clinically. Arm movements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
323
4
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(355 citation statements)
references
References 0 publications
25
323
4
3
Order By: Relevance
“…This indicates that movement smoothness is a result of a learned, coordinative process rather than a natural consequence of the structure of the neuromuscular system. Additionally, there is evidence that the segmented nature of stroke patients' arm movements can be attributed to a deficit in interjoint coordination (Levin, 1996). Taken with our observation that smoothness increases with recovery, the conclusion that smooth movement is a result of well developed coordination seems inescapable.…”
Section: Movement Smoothness Increases During Recoverymentioning
confidence: 56%
“…This indicates that movement smoothness is a result of a learned, coordinative process rather than a natural consequence of the structure of the neuromuscular system. Additionally, there is evidence that the segmented nature of stroke patients' arm movements can be attributed to a deficit in interjoint coordination (Levin, 1996). Taken with our observation that smoothness increases with recovery, the conclusion that smooth movement is a result of well developed coordination seems inescapable.…”
Section: Movement Smoothness Increases During Recoverymentioning
confidence: 56%
“…The formation and calibration internal models may be impeded by damage to areas of the brain where the model is formed, and also by the increased sensory noise which would result in poorer estimations of the arm's actual behaviour (Saunder and Knill, 2004). There is some evidence that there is a reduced ability to form an appropriate internal model following stroke, including altered feedforward control of the passive intersegmental joint torques during reaching movements (Beer et al, 2000) which would result in joint in-coordination (Levin, 1996) and poorer anticipatory control of arm movements to perturbations .…”
Section: Consequences Of Increased Neuromotor Noise On Trajectory Formentioning
confidence: 99%
“…Postural control during locomotion requires the integration of multiple sensory and motor pathways so that the central nervous system can coordinate the postural and movement components of the task 16) . Previous studies have shown that nervous system problems may occur with aging, and this may lead to less smooth movement [17][18][19] . These previous studies also suggested that movement smoothness is a result of learned coordination, and increases with recovery, because the segmented nature of a stroke patient's arm movement can be attributed to a deficit in interjoint coordination 18,19) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that nervous system problems may occur with aging, and this may lead to less smooth movement [17][18][19] . These previous studies also suggested that movement smoothness is a result of learned coordination, and increases with recovery, because the segmented nature of a stroke patient's arm movement can be attributed to a deficit in interjoint coordination 18,19) . Therefore, the results of the present study suggest that visual cues improve a deficit in interjoint coordination in the lower extremities.…”
Section: Discussionmentioning
confidence: 99%